INACTIVATION OF COMMON SPECIES OF FOOD POISONING BACTERIA BY ADDITION OF SOME CHEMICAL PRESERVATIVES - Farag, M.K . (Emirates Journal of Food and Agriculture, 1997)
Please see the scanned pdf version in full text